TOWARD A JUST TRANSITION? A FRAMEWORK FOR ANALYZING NICKEL-DRIVEN SOCIAL-ECOLOGICAL VIOLENCE - Yanuardi, Yanuardi; ZF Badoh, Ibrahim; Nugroho, Aryanto (Natapraja, 2024)
The global demand for nickel is surging, driven by the electric vehicle (EV) and energy storage sectors' push for decarbonization. This paper introduces a social-ecological violence framework to analyse the interconnected forms of violence within the nickel supply chain that are fuelled by surging demand from these sectors. Moving beyond direct human harm, it reveals how nickel extraction, processing, and trade generate overlapping violence against both communities and ecosystems. Examining case studies in nickel-rich countries and employing an eco-centric lens alongside interdisciplinary insights, the paper highlights the social and environmental impacts of the nickel supply chain, such as land dispossession, labour exploitation, pollution, and biodiversity loss, as systemic social-ecological violence. This framework offers a holistic understanding of the nickel supply chain's true costs, revealing feedback loops and power dynamics with the potential to improve extractive industry governance and foster social-ecological reflexivity. Ultimately, it contributes to a critical understanding of sustainability challenges in the energy transition and provides a basis for more sustainable and equitable resource governance towards social-ecological peace, defined by the absence of social-ecological violence and the presence of social-ecological justice and ecological integrity.